Enhancing Active Learning Through Gamified Platforms: Insights from the Implementation of Quizizz in English Language Education - Khayrullah, Nur Fitrawan; Umiyati, Umiyati; Samad, Ita Sarmita; Hasan, Hasan (Universitas Muhammadiyah Enrekang, 2024)
This study aims to determine the effect of the implementation of the Quizizz application on the English learning outcomes of students at MTs. DDI Enrekang. The population of this study was 34 grade VIII students at MTs. DDI Enrekang selected as samples using total samples. This study is quantitative with a pre-experimental one group method. From the output obtained the average pre-test score of students is 47 while for the post-test is 74. The results of the average post-test scores of students are included in the good category. Then if seen from the t-count> t-table which is 13.122> 1.692 then there is a significant influence between variable X on variable Y. So it can be concluded that Ha is accepted while Ho then in this study there is a significant influence in the implementation of the Quizizz application can improve students' English learning outcomes at MTs. DDI Enrekang. For authors who want to conduct similar research on students' English learning outcomes, it is expected to use the latest version of the Quizizz application.